Humanization of Pesantren Education: The Abraham Maslow Perspective - Mohammad Muchlis Solichin; Habibur Rahman (State Islamic Institute of Madura, 2022)
This article aims to review teaching learning process base on Maslow hirarchy need at modern pesantren in indonesia at Pesantren (Islamic Boarding School) Al Amin, Prenduan, Sumenep.This research uses a qualitative descriptive approach. The research subjects were the teachers who had taught at the pesantren for over 10 years..From the research it is identified that such learning practice includes: 1) the provision of physical environment and learning books as basic needs of student (the students of pesantren), (2) advocacy, encouragement and role model, psychological environment that will give opportunity for student to ask, express their opinions, give inputs and criticism so as to satisfy the need of safety to student when learning, 3) collaborative learning, assistance to student experiencing problems in their learning as the expression of affection to student, 4) reward to student recording excellent achievement, reward to criticism and input uttered by student as recognition to their self-esteem, 5) active learning, talent and potential development as self-actualization expression of student.